2013
DOI: 10.1097/igc.0b013e318286a95d
|View full text |Cite
|
Sign up to set email alerts
|

Six-Year Regression and Progression of Cervical Lesions of Different Human Papillomavirus Viral Loads in Varied Histological Diagnoses

Abstract: Objective This study aims to evaluate HPV viral load as a biomarker for triage into colposcopy and CIN2 therapy, in order to reduce the colposcopy referral rate and CIN2 over treatment in low resource settings. Methods In 1999, 1997 women aged 35–45 in Shanxi, China, received six cervical screenings with pathological confirmation. In 2005, 1461 histologically normal women, 99 with cervical intraepithelial neoplasia (CIN) grade 1 (CIN1), and 30 with CIN grade 2 or worse (CIN2+) were rescreened in a follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…Additionally, as more data has accumulated confirming the high regression rates of CIN2 lesions, especially for younger women [12,[23][24][25][26][27][28][29], it has increasingly become difficult to justify the inclusion of CIN2 lesions in the primary endpoint for cervical disease. These studies have indicated that almost half of all CIN2 lesions will regress spontaneously, with lesions that are negative for HPV types 16 and 18 having the highest rates of regression [25,29].…”
Section: B Panel Topic 1: Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, as more data has accumulated confirming the high regression rates of CIN2 lesions, especially for younger women [12,[23][24][25][26][27][28][29], it has increasingly become difficult to justify the inclusion of CIN2 lesions in the primary endpoint for cervical disease. These studies have indicated that almost half of all CIN2 lesions will regress spontaneously, with lesions that are negative for HPV types 16 and 18 having the highest rates of regression [25,29].…”
Section: B Panel Topic 1: Study Designmentioning
confidence: 99%
“…However, even for HR HPV infections, about 50% will spontaneously clear within 1-2 years [8]. HR HPV viral load has been identified as a major factor associated with cervical precancer, especially for the alpha 9 genotype family, which contains types 16,31,33,35,52, and 58 [9][10][11][12]. Therefore, HR HPV devices utilize a "clinical cutoff" (also known as a "clinical cutpoint"), where only HR infections with viral nucleic acid levels resulting in signals exceeding a certain threshold are reported as positive for HR HPV, in order to minimize identification of low viral load infections that have a high probability of spontaneous clearance.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 250 potentially eligible studies; 43 publications met the inclusion criteria (fig 1),6222324252627282930313233343536373839404142434445464748495051525354555657585960616263 but seven were duplicate reports of the same data 27283140505254. Of the 36 eligible studies (total of 3160 women), seven (19%) were randomised trials with suitable data in the non-experimental arm,22253339455762 16 (44%) were prospective cohort studies,6263032343536373841435155566063 and 13 (36%) were retrospective cohort studies23242942444647484953585961 (see supplementary table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 36 eligible studies (total of 3160 women), seven (19%) were randomised trials with suitable data in the non-experimental arm,22253339455762 16 (44%) were prospective cohort studies,6263032343536373841435155566063 and 13 (36%) were retrospective cohort studies23242942444647484953585961 (see supplementary table 2). The median follow-up was 16 months (range 3-72, interquartile range 7.6-27.4 months).…”
Section: Resultsmentioning
confidence: 99%
“…In 1999, 1,997 women aged 35 to 45 years were enrolled in Shanxi Province Cervical Cancer Screening Study I (SPOCCS I) study (14)(15)(16). They were nonpregnant and had no history of cervical screening or hysterectomy.…”
Section: Study Populationmentioning
confidence: 99%